Fintech Disruption: An Introspection - Sorin SOMITCA; Alina CRISMARIU (SOMITCA); Anamaria BORES (Communications of International Proceedings, 2021)
The actual and modern world is undergoing and facing major changes mainly due to the rapid development of technology. In the century we live in, digitalization is a phenomenon that the whole society is facing, being a factor in the development of human activity. We are contemporaries with major transformations, the revolution we are witnessing being considered the 4th industrial revolution, Industry 4.0, being in fact a revolution of digital or artificial intelligence. The pace at which change is evolving is unimaginably fast and immeasurably faster and on a larger scale than the previous Industrial Revolution of the early 19th century. Like an octopus, we can say that digitalization has spread its tentacles and has taken over the whole society, at all levels, generating the need for new skills, being interconnected with intellectual capital facilitating the creation of complex networks. The emergence and fulminant development of FinTech can be considered a milestone in the modernization of financial services, perhaps the greatest innovation in the last thirty years. According to the National Bank of Romania, FinTech is a technological innovation of financial services being a disruptive factor of the financial industry, competing directly with banks or other institutions in the financial sector or even acting in concert with them to deliver high quality financial services. In addition to the significant revenues generated, estimated to be somewhere at 92 billion in 2018, it is also given by the fact that it ensures the increase of the degree of financial inclusion, given the easier accessibility, flexibility and ease of use of some services. Even if it is difficult to recognize, the future in the financial industry is FinTech's.
Keywords: FinTech; Start-up; Financial Services; Disruption; Industry 4.0; Digitalization.